2017
DOI: 10.1038/mi.2016.81
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mucosal immunology

Abstract: Although largely deprived from exogenous stimuli in utero, the mucosal barriers of the neonate after birth are bombarded by environmental, nutritional, and microbial exposures. The microbiome is established concurrently with the developing immune system. The nature and timing of discrete interactions between these two factors underpins the long-term immune characteristics of these organs, and can set an individual on a trajectory towards or away from disease. Microbial exposures in the gastrointestinal and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 160 publications
(231 reference statements)
1
118
0
2
Order By: Relevance
“…As neonates are exposed to various Ags when born, it is believed that T cells are biased toward a T h 2 response to prevent excessive inflammation. As a T h 2 response can be detrimental to mycobacterial immunity, BCG vaccination of neonates may not fulfill its potential (105109). However, studies in human newborns and infants reported a T h 1 biased response following BCG immunization similar to immunized adults (110, 111).…”
Section: Adaptive Immune Responses To Bcg Vaccinationmentioning
confidence: 99%
“…As neonates are exposed to various Ags when born, it is believed that T cells are biased toward a T h 2 response to prevent excessive inflammation. As a T h 2 response can be detrimental to mycobacterial immunity, BCG vaccination of neonates may not fulfill its potential (105109). However, studies in human newborns and infants reported a T h 1 biased response following BCG immunization similar to immunized adults (110, 111).…”
Section: Adaptive Immune Responses To Bcg Vaccinationmentioning
confidence: 99%
“…Through the transfer of maternal antibodies, breast milk (BM) presents a unique opportunity to educate the developing infant mucosal immune system . Therefore, these BM‐derived antibodies may have significant implications for the transfer of protection provided against mucosal pathogens as shown for post‐natal mother‐to‐infant transfer of HIV and possibly against immune‐mediated diseases such as allergies.…”
Section: Introductionmentioning
confidence: 99%
“…However, type 2 responses in the absence of helminth infections can also have beneficial roles: circulating IgE specific to venom toxins, which can cause dangerous anaphylaxis on exposure, can also be protective with release of mast cell proteases that degrade venom toxins and counteract the venom's detrimental effects . During pregnancy, the type 2 cytokine milieu in the womb protects the “non‐self” foetus from abortion (which conversely is linked to increased Th1/17 responses) . Finally, perinatal type 2 responses in the lung are required for establishment of lung homoeostasis and development of anti‐inflammatory type 2 macrophages .…”
Section: Helminth Infections Damage and Type 2 Immune Responsesmentioning
confidence: 99%